2009
DOI: 10.1002/adfm.200900926
|View full text |Cite
|
Sign up to set email alerts
|

Transistor Paint: Environmentally Stable N‐alkyldithienopyrrole and Bithiazole‐Based Copolymer Thin‐Film Transistors Show Reproducible High Mobilities without Annealing

Abstract: New solution processable 4‐(2‐hexyldecan)‐4H‐bisthieno[2,3‐d:3′,2′‐b]pyrrole and 4,4′‐dialkyl‐2,2′‐bithiazole‐based copolymers (PBTzDTPs) are synthesized with excellent FET performance. These novel copolymers have considerable potential in printable electronics as they have high charge carrier mobilities, excellent air stability, good solution processibility, and no requirement for post‐deposition thermal annealing, all requirements for this field of application. The thin film transistors fabricated from PBTzD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…[ 37 , 38 ] A similar result was obtained on a 3% strained polyimide substrate, which demonstrates the suitabilty of smectic compounds for fl exible plastic electronics. [ 39 ] Photoalignment has been used to align a phenylenethiophene molecule, compound 12 , with a high-temperature smectic phase. The magnitude of the mobility was enhanced when the direction of electronic transport was parallel to the direction of the intermolecular hops (perpendicular to the molecular rods).…”
Section: Polymer Liquid Crystals For Ofetsmentioning
confidence: 99%
“…[ 37 , 38 ] A similar result was obtained on a 3% strained polyimide substrate, which demonstrates the suitabilty of smectic compounds for fl exible plastic electronics. [ 39 ] Photoalignment has been used to align a phenylenethiophene molecule, compound 12 , with a high-temperature smectic phase. The magnitude of the mobility was enhanced when the direction of electronic transport was parallel to the direction of the intermolecular hops (perpendicular to the molecular rods).…”
Section: Polymer Liquid Crystals For Ofetsmentioning
confidence: 99%
“…On the other hand, smoother polymer films provide a higher uniformity due to smaller grain microstructures and finally higher charge carrier mobilities. 49 This may be a reason why PBDTTQ-3 has a higher mobility than PAPhTQ.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has recently been demonstrated that both highly polar diketopyrrolopyrrole (DPP) and benzothiadiazole (BT) containing donoracceptor polymers are able to afford even higher carrier mobilities, 6,7,8 despite having apparently less ordered microstructures, and functional groups that have previously been expected to potentially act as charge traps. These results suggest that one dimensional charge transport along the polymer chains may dominate in these low ordered systems.…”
Section: Introductionmentioning
confidence: 99%